2018
DOI: 10.4103/ijpsym.ijpsym_205_18
|View full text |Cite
|
Sign up to set email alerts
|

Is menstrual Psychosis a Forgotten Entity?

Abstract: The connection between menstruation and psychosis has been recognized since the 18 th Century. However, there are few case reports available in modern times describing about 30 patients with this condition. The psychosis may occur in the premenstrual phase in some patients and in others it begins with the onset of menses. Polymorphic psychosis is the commonly described clinical picture in these patients with an admixture of mood symptoms and psychotic symptoms. We describe a 42-year old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In our case, anxiety and mood symptoms were observed along with psychotic symptoms. It has been reported that in some cases with MP, symptoms of over-dependence or regression to family members may be observed (8,9). In our case, fear, confusion, dependence on family members and regression symptoms were observed.…”
Section: Introductionsupporting
confidence: 52%
“…In our case, anxiety and mood symptoms were observed along with psychotic symptoms. It has been reported that in some cases with MP, symptoms of over-dependence or regression to family members may be observed (8,9). In our case, fear, confusion, dependence on family members and regression symptoms were observed.…”
Section: Introductionsupporting
confidence: 52%
“…These studies retrospectively rely on a patient's self-reported or clinicianobserved experiences over several years or decades. In all but one 37 of the identified case studies, the authors reported recurrent psychosis during the premenstrual phase. 28,29,[32][33][34]36,38 Often, symptom onset occurred at menarche.…”
Section: Psychosismentioning
confidence: 99%
“…It may shorten the length of episodes but has not demonstrated the ability to prevent recurrence of episodes 8. In some instances, menstrual psychosis may be unresponsive to neuroleptics completely, both in its oral and long-acting injectable forms 9. Therefore, it is worth considering a treatment plan that takes all these factors into account.…”
Section: Discussionmentioning
confidence: 99%